Parallel complex event processing system based on S4 framework - Hao CHEN; Yu LI; Song-lin HU; Ying LIANG (Tongxin xuebao)
There was a throughput bottleneck for complex event processing in only one computer,and the existing general-purpose parallel framework was not suitable for complex event processing system.Based on the analysis of existing parallel technology,fourteen kinds of complex event processing operator and a parallel framework by operator for complex event processing system were proposed,the event stream load triage based on operator was given.S4 system for parallel complex event processing system was utilized,provided greater reliability and throughput than stand-alone operation.Through the cluster experiments show that,within a certain range,the throughput of the system can be increased with the number of cluster nodes linear growth.